Note on the work function algorithm - Csaba, Béla (Acta Cybernetica, 2000)
We prove that the work function algorithm is (n-l)-competitive for the k-server problem, where n is the number of points in the metric space. This gives improved upper bounds when k +3 < n < 2k-1; in particular, it shows that the work function algorithm is optimal for k = n-1. Recently this result was proved independently by Koutsoupias in [K].